2016
DOI: 10.4236/ajps.2016.717215
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Variation for Low Striga Germination Stimulation in Sorghum “<i>Sorghum bicolor</i> (L.) Moench” Landraces from Eritrea

Abstract: Sorghum (Sorghum bicolour (L.) Moench), the second most important staple crop in Sub-Saharan Africa (SSA) after maize, is well adapted to marginal environments of drought stress and high temperatures. But besides drought stress, the obligate root-parasitic flowering plant Striga hermonthica is an equally economically important biotic stress in agro-ecological zones where soils are marginal. Notwithstanding widespread and intense Striga infestation, genetic variations in defence mechanisms against the parasite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(19 reference statements)
2
6
0
Order By: Relevance
“…Higher maximum germination distances together with higher numbers of induced germinated Striga seeds suggest higher amounts of secreted strigolactones in sorghum genotypes, an indication of potential susceptibility of the genotypes to Striga weed. These findings compare well with those of Yohannes et al (2016) who evaluated sorghum genotypes for secretion of low Striga germination stimulant and Reda et al (1994) who screened maize genotypes for low Striga asiatica stimulant production. Yohannes et al (2016) reported reduced secretion of germination stimulant and subsequent Striga resistance in the evaluated landraces compared to the commercial checks while Reda et al (1994) reported a high correlation between maximum germination distance and numbers of induced germinated Striga seeds.…”
Section: Striga Seeds In Agar Gel Experimentssupporting
confidence: 81%
See 1 more Smart Citation
“…Higher maximum germination distances together with higher numbers of induced germinated Striga seeds suggest higher amounts of secreted strigolactones in sorghum genotypes, an indication of potential susceptibility of the genotypes to Striga weed. These findings compare well with those of Yohannes et al (2016) who evaluated sorghum genotypes for secretion of low Striga germination stimulant and Reda et al (1994) who screened maize genotypes for low Striga asiatica stimulant production. Yohannes et al (2016) reported reduced secretion of germination stimulant and subsequent Striga resistance in the evaluated landraces compared to the commercial checks while Reda et al (1994) reported a high correlation between maximum germination distance and numbers of induced germinated Striga seeds.…”
Section: Striga Seeds In Agar Gel Experimentssupporting
confidence: 81%
“…These findings compare well with those of Yohannes et al (2016) who evaluated sorghum genotypes for secretion of low Striga germination stimulant and Reda et al (1994) who screened maize genotypes for low Striga asiatica stimulant production. Yohannes et al (2016) reported reduced secretion of germination stimulant and subsequent Striga resistance in the evaluated landraces compared to the commercial checks while Reda et al (1994) reported a high correlation between maximum germination distance and numbers of induced germinated Striga seeds. Both Yohannes et al (2016) and Reda et al (1994) (Mohamed et al, 2010).…”
Section: Striga Seeds In Agar Gel Experimentssupporting
confidence: 81%
“…Lately, the use of genetic defense mechanisms, such as use of resistant or tolerant genotypes, has become a viable and cost‐effective method to reduce maize yield losses caused by Striga (Rodenburg and Bastiaans, 2011; Ransom et al, 2012; Yohannes et al, 2016). Genetic defense to Striga species has been found to exist in cereal crops, such as sorghum and rice ( Oryza sativa L.) (Oswald, 2005; Badu‐Apraku et al, 2013; Samejima et al, 2016).…”
mentioning
confidence: 99%
“…Screen house technique has been used to screen maize genotypes for tolerance / resistance to Striga (Chitagu et al., 2014; Nyakurwa et al., 2018; Yohannes et al., 2016). In screen houses, screening for varietal resistance has been performed using pots and buried seed studies (Eplee & Norris, 1987; Rao, 1985; Sand et al., 1990).…”
Section: Methods For Screening Striga Resistance In Maizementioning
confidence: 99%